The Victims Rights & Conditions Protection On Trafficting Crime Through The Implementation Of Restitutions - Sefin Anggi Riyantika; Jawade Hafidz (Law Development Journal, 2021)
This study aims to further analyze the protection of victims of the crime of human trafficking who have not been able to accommodate the rights and losses of victims. The approach method used is sociological juridical. Based on the analysis of the existing findings, it is clear that the implementation of the protection of the rights of victims of human trafficking has not been running effectively due to unclear restitution arrangements, both in terms of magnitude and related to criminal arrangements for replacement of restitution. The Crime of Human trafficking is a crime against humanity that can harm a person both materially and physically and mentally. In addition, it is necessary for victims of human trafficking to obtain protection of their rights, which in this case can be done through restitution. In practice, the amount of restitution is not clearly defined. In addition, the existence of a criminal substitute for compensation, which in this case includes restitution, makes the implementation of restitution difficult for victims of human trafficking. Such conditions clearly contradict the First Precepts, Second Precepts, and Fifth Precepts of Pancasila, as well as the Fourth Paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia as the purpose of the state, as well as Article 28D paragraph (1) and Article 28G Paragraph (1 ) and Paragraph (2) of the 1945 Constitution of the Republic of Indonesia as the basic foundation related to the human rights of victims of human trafficking, and as a legal ratio in law in Indonesia.